Correlates of Self-Rated Health and Self-Rated Mental Health in Older Chinese Americans. Issue 4 (6th June 2016) - Jang, Yuri; Huang, Ya-Ching; Yoon, Hyunwoo; Lin, Shumin
Abstract : The present study examined the factors associated with self-rated health (SRH) and self-rated mental health (SRMH) in a sample of 108 older Chinese Americans (MeanAge  = 70.6, SD  = 7.70). SRH and SRMH were highly associated with each other. In the multiple regression models, chronic conditions and functional disability emerged as significant predictors of poor SRH and SRMH. However, the significance of depressive symptoms was only obtained in the model of SRMH. The findings reflect the body–mind connection among older Chinese Americans and provide implications for integrative health promotion efforts.